Source, harvesting, conservation status, threats and management of indigenous plant used for respiratory infections and related symptoms in the Limpopo Province, South Africa - SEBUA SILAS SEMENYA; ALFRED MAROYI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Semenya SS, Maroyi A. 2019. Source, harvesting, conservation status, threats and management of indigenous plant used for respiratory infections and related symptoms in the Limpopo Province, South Africa. Biodiversitas 20: 789-810. This survey explored Bapedi traditional healer’s (THs) practices pertinent to native plants used to treat respiratory infections (RIs) and related symptoms (RSs). Semi-structured questionnaires and participatory observations were used to gather information from 240 THs in the Limpopo Province, South Africa. 186 plants from 75 families were harvested by these THs, mainly from the communal lands (81.2%), throughout the year. Plant parts used for RIs and RSs remedies was destructively harvested in wilderness compared to homegardens. Most (n=174) species from which these parts are obtained appears on the South African National Red Data List of plants, with 88.5% having a list concern status. This included Adansonia digitata, Boscia albitrunca, Catha edulis, Securidaca longepedunculata and Sclerocarya birrea which are also protected under the National Forest Act of 1998 (Act no. 84 of 1998). A further, 8.6% (n=15) of Red Data Listed plants are of conservation concern, with various status namely near threatened (38.3%), declining (20%), data deficient (13.3%), critically endangered and vulnerable (3.3%, for each), as well as endangered (6.6%). There were both consensus and disjunction amongst THs and Red Data List regarding the status of plants in the wild. This study provides valuable data for the conservation of medicinal plants in Limpopo Province.